Konsep Ilmu Menurut Al-Ghazali Perspektif Filosofis: Aspek Ontologi, Epistemologi, Aksiologi - Ahsanul Anam (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2022)
Al-Ghazali is one of the most phenomenal Islamic figures, he is known by various groups both in the Islamic and non-Islamic worlds. As a very productive Islamic figure, al-Ghazali produced many great works as the fruit of his broad and deep thoughts. His knowledge is very broad spanning various fields of study. In this article, the author describes al-Ghazali's thoughts about science which is the embryo of character education which is currently a trend in the world of education in Indonesia. The effort of writing this article is also to open the horizons of al-Ghazali's scientific concepts which of course have been studied by many people. It's just that the author tries to systematize this article through a philosophical approach, namely aspects of ontology, epistemology and axiology. The concept of science according to al-Ghazali is an intellectual endeavor to see the horizon of the concept of science that is approached through this philosophical approach. That the science or science in question is comprehensive. This means that in al-Ghazali's perspective, science is not only oriented to intellectual intelligence. However, science is also oriented towards emotional and spiritual intelligence as well. Psychological-pedagogic review is used to see the point of view of science in shaping and giving birth to emotional intelligence. Where at this time the world of education is experiencing disorientation in its educational goals which should be able to shape and create a complete human being.